Assessment of the Potential of CDK2 Inhibitor NU6140 to Influence the Expression of Pluripotency Markers NANOG, OCT4, and SOX2 in 2102Ep and H9 Cells - Ade Kallas; Martin Pook; Annika Trei; Toivo Maimets (International Journal of Cell Biology)
As cyclin-dependent kinases (CDKs) regulate cell cycle progression and RNA transcription, CDKs are attractive targets for creating cancer cell treatments. In this study we investigated the effects of the small molecular agent NU6140 (inhibits CDK2 and cyclin A interaction) on human embryonic stem (hES) cells and embryonal carcinoma-derived (hEC) cells via the expression of transcription factors responsible for pluripotency. A multiparameter flow cytometric method was used to follow changes in the expression of NANOG, OCT4, and SOX2 together in single cells. Both hES and hEC cells responded to NU6140 treatment by induced apoptosis and a decreased expression of NANOG, OCT4, and SOX2 in surviving cells. A higher sensitivity to NU6140 application in hES than hEC cells was detected. NU6140 treatment arrested hES and hEC cells in the G2 phase and inhibited entry into the M phase as evidenced by no significant increase in histone 3 phosphorylation. When embryoid bodies (EBs) formed from NU6104 treated hES cells were compared to EBs from untreated hES cells differences in ectodermal, endodermal, and mesodermal lineages were found. The results of this study highlight the importance of CDK2 activity in maintaining pluripotency of hES and hEC cells and in differentiation of hES cells.